Evaluation of Factors Influencing the Successful Implementation of the Independent Learning Curriculum at State Vocational High School 3 Pekanbaru - Dimas Sunata; Sumarno Sumarno; Hendripides Hendripides (CV. Rayyan Dwi Bharata, 2023)
This study aims to identify and obtain information about the analysis of the implementation of the independent learning curriculum in public vocational high schools (SMKN) 3 Pekanbaru. The method used in this study is a qualitative descriptive method, which describes the subject about the situation and data obtained during observations and questions so that it becomes useful information and is easily understood by readers. The samples in this study were school principals, vice-curriculum administrators and subject teachers. Data was collected by conducting interviews, observation and documentation. The results showed that the analysis of the implementation of the independent learning curriculum at the public vocational high school (SMKN) 3 Pekanbaru has been carried out optimally and is ongoing, although there are still obstacles in its implementation. The key to success in implementing the independent learning curriculum is that the principal and teachers must have the will to make changes. The principal as a leader must be able to change the mindset of the human resources in the school to want to make changes and provide equipment for each major class so that this independent curriculum can be implemented.